STEERING CONTROLLED HEADLIGHTS FOR ENHANCED VISIBILITY AND ADVANCING AUTOMOTIVE SAFETY: REVIEW (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The proposed work focuses on developing a steering-controlled headlight system to enhance nighttime driving safety through adaptive lighting. The system employs two 300 RPM gear motors, each controlling the horizontal movement of individual LED headlights. These high-torque motors ensure precise headlight adjustment in response to steering inputs, providing optimal road illumination during curves and turns. The headlight’s movement is controlled by two-way switches linked to the steering mechanism, which activate the motors to adjust the headlights' direction based on the steering wheel position. In the neutral position, the headlights remain centred, offering forward illumination. The integration of these gear motors ensures accurate, swift headlight response with minimal power consumption, enhancing overall vehicle efficiency. This proposed system significantly improves visibility and driver safety, making nighttime driving safer and more comfortable by adjusting the headlights in real-time to the vehicle's steering direction.